Maternal compliance with complete basic immunization: The role of knowledge, family support, and anxiety - Faradila, Putri; Andarsini, Mia Ratwita; Farizi, Sofia Al; Sulistiawati, Sulistiawati (Institute of Computer Science (IOCS), 2025)
Complete basic immunization plays a crucial role in public health efforts to protect infants from infectious diseases and to decrease child morbidity and mortality. Despite its importance, the coverage of complete basic immunization in the Socah Community Health Center area remained low at 44.7%, which did not meet the national standard. This situation reflects inadequate maternal adherence in providing immunizations for their children. The present study aimed to examine the association between maternal knowledge, family support, and anxiety levels with their adherence to complete basic immunization. An analytic observational design with a cross-sectional approach was utilized. Eighty-three mothers with children aged 12–24 months were chosen through proportionate cluster random sampling. Data collection was conducted using structured questionnaires and immunization record reviews, and analyzed through the Chi-square test at a significance level of 0.05. Findings revealed significant associations between knowledge (p = 0.005), family support (p = 0.039), and anxiety (p = 0.007) and maternal adherence to immunization. Mothers possessing better knowledge, stronger family backing, and lower anxiety levels tended to follow the immunization schedule more consistently. The study suggests strengthening educational interventions and psychological support programs for mothers and families to enhance complete basic immunization coverage in the community.